Analysis of the Sense of Coherence, anxiety and depression in graduate students: Follow-up study (Research, Society and Development, 2021)
Interest in research that measures anxiety, depression and resilience among graduate students in the health area during the course has increased in the last years. This follow-up analytical study evaluated the presence of anxiety, depression and a sense of coherence (resilience) in graduate students at UPE and UFPB in Dentistry and other courses (Nursing, Physical Education, Hebiatry, Forensic Skills). A socio-economic questionnaire was used, followed by the Sense of Coherence questionnaire (SOC) that measures the individual's ability to be adaptive to daily events. The State-Trait Anxiety Inventory (STAI) measured state-anxiety (about an event) and trait-anxiety (personal characteristic). The Beck Depression Inventory (BDI-II) was the fourth instrument in this research. The first data collection was performed in the inaugural classes of the 2019/2020 master classes, the second data collection was performed at the time of the students' qualification. Research participants showed an increase in the sense of coherence, an increase in anxiety-state levels from 14.6% to 36.7% (p